2011
DOI: 10.3109/02652048.2011.559287
|View full text |Cite
|
Sign up to set email alerts
|

A novel microparticulate vaccine for melanoma cancer using transdermal delivery

Abstract: In this study, we formulated a microparticulate melanoma cancer vaccine via the transdermal route. The vaccine was delivered using microneedle-based Dermaroller® which is available for cosmetic purposes. Unlike subcutaneous injections, administration using microneedles is painless and in general can increase the permeability of many compounds ranging in size from small molecules to proteins and microparticles that do not normally penetrate the skin. The vaccine microparticles were taken up by the antigen prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Spray-drying complies with both [38,39]. Moreover, when spray-drying is compared to other drying processes commonly used in industry such as freeze-drying, it is shorter and cheaper because it does not involve deep cooling, usually associated with great energy consumption [32,[40][41][42][43].…”
Section: Main Advantages Of the Spray-drying Processmentioning
confidence: 97%
See 1 more Smart Citation
“…Spray-drying complies with both [38,39]. Moreover, when spray-drying is compared to other drying processes commonly used in industry such as freeze-drying, it is shorter and cheaper because it does not involve deep cooling, usually associated with great energy consumption [32,[40][41][42][43].…”
Section: Main Advantages Of the Spray-drying Processmentioning
confidence: 97%
“…Finally, the particles loaded with drugs obtained by spray-drying could be administered by different routes such as oral [127][128][129][130][131][132], pulmonary [12,23,82,133,134), ophthalmic [93,111,135], parenteral [22,38,136], nasal [60,120,121,137], and vaginal [138], stressing its great In vitro tests showed that their mucoadhesion was 2-fold higher than that of a hydroxyethylcellulose gel formulation [138].…”
Section: Different Routes Of Administration Of Drug-loaded Polymeric mentioning
confidence: 99%
“…50 Much research has been carried out in the field of transdermal vaccine delivery in recent years. Bhowmik et al 51 formulated a microparticulate whole cell lysate vaccine composed of melanoma cell line antigens, in a biodegradable matrix of bovine serum albumin (BSA) and other sustained-release polymers. The particles ranged in size from 0.165 to 1.5 mm.…”
Section: Transdermal Routementioning
confidence: 99%
“…The group treated with DT coadministered with CT showed similar IgG levels to those treated subcutaneously with DT-alum. N-trimethyl chitosan also proved benefi cial in boosting the immune response to DT following MN pretreatment when in solution with the antigen, although no improvement in immune response was seen from DT-loaded nanoparticles of N-trimethyl chitosan [ 54 ].…”
Section: Poke and Patchmentioning
confidence: 99%
“…The impact of transdermal vaccination on the development of melanoma was reported by Bhowmik et al (2011), who delivered a novel microparticulate vaccine to the skin following puncture using of MN-based Dermaroller ® [ 55 ]. Mice were grouped into four groups; group one was treated using Dermaroller ® microneedles, followed by application of microparticles containing encapsulated antigen obtained from S-91 melanoma cancer cells.…”
Section: Poke and Patchmentioning
confidence: 99%